2019
DOI: 10.3390/atmos10060321
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Evolution over Belgium by 2100 and Sensitivity to Convective Schemes Using the Regional Climate Model MAR

Abstract: The first aim of this study is to determine if changes in precipitation and more specifically in convective precipitation are projected in a warmer climate over Belgium. The second aim is to evaluate if these changes are dependent on the convective scheme used. For this purpose, the regional climate model Modèle Atmosphérique Régional (MAR) was forced by two general circulation models (NorESM1-M and MIROC5) with five convective schemes (namely: two versions of the Bechtold schemes, the Betts–Miller–Janjić sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Hourly weather data [air temperature (T), relative humidity (RH), and rainfall (R)] from January 2018 to December 2020 were computed using the regional climate model Modèle Atmosphérique Régional (MAR) version 3.9 [ 33 , 34 ]. The MAR was run at a horizontal resolution of 5-km over a domain covering the whole Belgium, with the first 24 h from the daily forecast run (00h GMT) of the global weather forecast model Global Forecast System (GFS) being used as the lateral boundary conditions of MAR.…”
Section: Methodsmentioning
confidence: 99%
“…Hourly weather data [air temperature (T), relative humidity (RH), and rainfall (R)] from January 2018 to December 2020 were computed using the regional climate model Modèle Atmosphérique Régional (MAR) version 3.9 [ 33 , 34 ]. The MAR was run at a horizontal resolution of 5-km over a domain covering the whole Belgium, with the first 24 h from the daily forecast run (00h GMT) of the global weather forecast model Global Forecast System (GFS) being used as the lateral boundary conditions of MAR.…”
Section: Methodsmentioning
confidence: 99%
“…MAR has originally been applied to represent the climate of polar regions, but it has then been adapted to temperate climates such as Belgium (e.g. Wyard et al, 2017 ;Doutreloup et al, 2019).…”
Section: A the Mar Modelmentioning
confidence: 99%
“…The RCM used in this study is the MAR model which, although being initially designed for polar regions (Gallée and Schayes, 1994) such as Greenland (Fettweis et al, 2013) or Antarctica (Kittel et al, 2018), was recently adapted and applied to the temperate climate of Belgium (Fettweis et al, 2017;Wyard et al, 2017Wyard et al, , 2018Doutreloup et al, 2019aDoutreloup et al, , 2019b. MAR is a hydrostatic primitive equation model in which convection is parametrized according to Bechtold et al (2001).…”
Section: The Mar Modelmentioning
confidence: 99%
“…Therefore, despite the significant improvements implemented in the convective scheme of MARv3.8 (Fettweis et al, 2017;Wyard et al, 2018), substantial biases remain in the simulation of convective precipitation. Doutreloup et al (2019aDoutreloup et al ( , 2019b tested the sensitivity of MARv3.9 to five different convective schemes and concluded that none of these convective schemes significantly improves the representation of convective precipitation events. Given the projected increase in convective winter precipitation, using a non-hydrostatic RCM could provide some improvement to the reliability of the projected wintertime precipitation, although the role of convective precipitation remains very limited in the winter months compared to other types of precipitation.…”
Section: Uncertainties Linked To Convection Parameterizationmentioning
confidence: 99%